The Cenotaph, Port of Spain - (:unkn) unknown (Bon Genie Ltd., Trinidad, 2010)
Description on back of card: “The Cenotaph, Port of Spain’s Memorial to the sons of Trinidad who died in 2 world wars, is located at the northern edge of Port of Spain.” A few fine branches of a vibrant scarlet, ornamental Flamboyant and its fruit - long, flat, woody pods – line the top of this photograph of the war monument at War Memorial Park, known by nationals as “Memorial Park”. This majestic monument was placed here in honour of Trinidad and Tobago nationals who served and died in World Wars I and II, 1914-1918 and 1939-1945. The mountains, in the background, look a painted, bright turquoise. The trees surrounding the monument are vibrant green and some of them have yellow flowers. There are two benches in the foreground, just off one of the monument’s four pathways.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Royal poinciana--Trinidad and Tobago; Monuments--Trinidad and Tobago; Memorials--Trinidad and Tobago; 1977; Pride-of-Barbados (Plant)--Trinidad and Tobago; War memorials--Trinidad and Tobago; Historic sites--Trinidad and Tobago; War Memorial Park